The Role of Self-Regulation in Forgiveness: A Regulatory Model of Forgiveness - Ho, Man Yee; Van Tongeren, Daryl R.; You, Jin (Frontiers in Psychology, 2020)
Forgiveness is an emotion regulation process that is important for both physical and mental health. Given its benefits, studying the facilitation of forgiveness is important. Researchers have already demonstrated the relationship between self-control and forgiveness. However, in this study, we aim to extend previous research by examining the regulating processes of forgiveness and the possible mediating role of emotion regulation in the relationship between self-regulatory strength and forgiveness. University students (N = 317) in Hong Kong who were recruited to participate in this study completed an online survey. The results of this study indicated that both self-regulatory strength and emotion regulation were significant predictors of forgiveness. Interestingly, cognitive reappraisal significantly mediated the association between self-regulatory fatigue and forgiveness. This suggests a potential self-regulation mechanism that leads to a prorelationship response and provides evidence for a regulatory model of forgiveness.